Ecosystem restoration and belowground multifunctionality: A network view. Issue 5 (19th May 2022) - Tian, Dashuan; Xiang, Yangzhou; Seabloom, Eric; Chen, Han Y. H.; Wang, Jinsong; Yu, Guirui; Deng, Ye; Li, Zhaolei; Niu, Shuli
Abstract: Ecological restoration is essential to reverse land degradation worldwide. Most studies have assessed the restoration of ecosystem functions individually, as opposed to a holistic view. Here we developed a network‐based ecosystem multifunctionality (EMF) framework to identify key functions in evaluating EMF restoration. Through synthesizing 293 restoration studies (2900 observations) following cropland abandonment, we found that individual soil functions played different roles in determining the restoration of belowground EMF. Soil carbon, total nitrogen, and phosphatase were key functions to predict the recovery of belowground EMF. On average, abandoned cropland recovered ~19% of EMF during 18 years. The restoration of EMF became larger with longer recovery time and higher humidity index, but lower with increasing soil depth and initial soil carbon. Overall, this study presents a network‐based EMF framework, effectively helping to evaluate the success of ecosystem restoration and identify the key functions.